The Potential Benefits of Palmitoylethanolamide in Palliation: A Qualitative Systematic Review. (December 2019) - Davis, Mellar P.; Behm, Bertrand; Mehta, Zankhana; Fernandez, Carlos
Palmitoylethanolamide (PEA) is a nutraceutical endocannabinoid that was retrospectively discovered in egg yolks. Feeding poor children with known streptococcal infections prevented rheumatic fever. Subsequently, it was found to alter the course of influenza. Unfortunately, there is little known about its pharmacokinetics. Palmitoylethanolamide targets nonclassical cannabinoid receptors rather than CB1 and CB2 receptors. Palmitoylethanolamide will only indirectly activate classical cannabinoid receptors by an entourage effect. There are a significant number of prospective and randomized trials demonstrating the pain-relieving effects of PEA. There is lesser evidence of benefit in patients with nonpain symptoms related to depression, Parkinson disease, strokes, and autism. There are no reported drug–drug interactions and very few reported adverse effects from PEA. Further research is needed to define the palliative benefits to PEA.